2020
DOI: 10.3390/ijerph17249401
|View full text |Cite
|
Sign up to set email alerts
|

COVID-Well: Evaluation of the Implementation of Supported Wellbeing Centres for Hospital Employees during the COVID-19 Pandemic

Abstract: Supported Wellbeing Centres have been set up in UK hospital trusts in an effort to mitigate the psychological impact of COVID-19 on healthcare workers, although the extent to which these are utilised and the barriers and facilitators to access are not known. The aim of the study was to determine facility usage and gather insight into employee wellbeing and the views of employees towards this provision. The study included (i) 17-week service use monitoring, (ii) employee online survey with measures of wellbeing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(115 citation statements)
references
References 36 publications
6
107
1
1
Order By: Relevance
“…In private companies [ 24 , 71 ] and public institutions [ 124 ], internal marketing practices generate an increase in employee satisfaction. For instance, the implementation of internal marketing led to positive results among 355 employees within the hospitality industry, thus marking its significant and positive impact on job satisfaction [ 5 ]. Similar results were obtained from research involving Greek hospitals [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In private companies [ 24 , 71 ] and public institutions [ 124 ], internal marketing practices generate an increase in employee satisfaction. For instance, the implementation of internal marketing led to positive results among 355 employees within the hospitality industry, thus marking its significant and positive impact on job satisfaction [ 5 ]. Similar results were obtained from research involving Greek hospitals [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 global pandemic has become a reality in managing the processes of organizational health, and in the recent management of human resources [1][2][3], with direct implications on employee satisfaction and performance [4], together with the effects and vast repercussions on employee wellbeing. Managers [5] and authorities [6] are not always fully aware of these effects. To remain in the market, organizations from various industries have devoted considerable effort to adapt to the turbulent conditions in their dynamics, and to identify solutions and proper strategies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the wellbeing centres and wellbeing buddy role is provided elsewhere [25]. Two wellbeing centres opened on 6 April 2020 and provided relaxing rest spaces for hospital employees during the COVID-19 pandemic.…”
Section: The Supported Wellbeing Centresmentioning
confidence: 99%
“…However, it has been found that some healthcare workers unable to work on the frontline during the pandemic not only felt guilt, but perceived themselves to be undervalued, which demonstrates the importance of colleagues and managers in healthcare organizations proactively acknowledging their contribution to the pandemic response [57] to demonstrate inclusion and equity in recognition of effort. Despite the positive or negative emotions experienced, research conducted concurrently at the same hospital Trust demonstrated high levels of staff dedication and commitment to their roles with the NHS during the pandemic [25].…”
Section: Emotional Impacts Of Covid-19mentioning
confidence: 99%
“…However, the actual attempts to implement these guidelines resulted in a variety of formats, time frames, and practical solutions. This included both onsite and online format of support (41,42), centralized nationwide top-down interventions (43) and local support models developed for a particular hospital or unit (21), as well as initiatives based on established protocols (24) and approaches where the topics of support were dynamically adjusted according to the current needs (19). This large variety of models and protocols for psychological support calls for more integrative and reflective analyses of different approaches, their advantages, and problems (44).…”
Section: Discussionmentioning
confidence: 99%